Hearing Loss, Loneliness, and Social Isolation: A Systematic Review. (10th March 2020) - Shukla, Aishwarya; Harper, Michael; Pedersen, Emily; Goman, Adele; Suen, Jonathan J.; Price, Carrie; Applebaum, Jeremy; Hoyer, Matthew; Lin, Frank R.; Reed, Nicholas S.
Abstract : Objective: Social isolation and loneliness are associated with increased mortality and higher health care spending in older adults. Hearing loss is a common condition in older adults and impairs communication and social interactions. The objective of this review is to summarize the current state of the literature exploring the association between hearing loss and social isolation and/or loneliness. Data Sources: PubMed, Embase, CINAHL Plus, PsycINFO, and the Cochrane Library. Review Methods: Articles were screened for inclusion by 2 independent reviewers, with a third reviewer for adjudication. English‐language studies of older adults with hearing loss that used a validated measure of social isolation or loneliness were included. A modified Newcastle‐Ottawa Scale was used to assess the quality of the studies included in the review. Results: Of the 2495 identified studies, 14 were included in the review. Most of the studies (12/14) were cross‐sectional. Despite the heterogeneity of assessment methods for hearing status (self‐report or objective audiometry), loneliness, and social isolation, most multivariable‐adjusted studies found that hearing loss was associated with higher risk of loneliness and social isolation. Several studies found an effect modification of gender such that among women, hearing loss was more strongly associated with loneliness and social isolation than among men. Conclusions: Our findings that hearing loss is associated with loneliness and social isolation have important implications for the cognitive and psychosocial health of older adults. Future studies should investigate whether treating hearing loss can decrease loneliness and social isolation in older adults.